Exploration of hydroxymethylation in Kagami-Ogata syndrome caused by hypermethylation of imprinting control regions - Matsubara, Keiko (Clin Epigenetics, 2015)
BACKGROUND: 5-Hydroxymethylcytosine (5hmC), converted from 5-methylcytosine (5mC) by ten-eleven translocation (Tet) enzymes, has recently drawn attention as the “sixth base” of DNA since it is considered an intermediate of the demethylation pathway. Nonetheless, it remains to be addressed how 5hmC is linked to the development of human imprinting disorders. In this regard, conventional bisulfite (BS) treatment is unable to differentiate 5hmC from 5mC. It is thus hypothesized that BS conversion-derived “hypermethylation” at imprinting control regions (ICRs), which may cause imprinting disorders, would in fact be attributable to excessively increased levels of 5hmC as well as 5mC. To test this hypothesis, we applied the newly developed oxidative BS (oxBS) treatment to detect 5hmC in blood samples from Kagami-Ogata syndrome (KOS14) patients caused by an epimutation (hypermethylation) of two differentially methylated regions (DMRs) functioning as ICRs, namely, IG-DMR and MEG3-DMR. FINDINGS: oxBS with pyrosequencing revealed that there were few amounts of 5hmC at the hypermethylated IG-DMR and MEG3-DMR in blood samples from KOS14 patients. oxBS with genome-wide methylation array demonstrated that global levels of 5hmC were very low with similar distribution patterns in blood samples from KOS14 patients and normal controls. We also confirmed the presence of large amounts of 5hmC in the brain sample from a normal control. CONCLUSIONS: 5hmC is not a major component in abnormally hypermethylated ICRs or at a global level, at least in blood from KOS14 patients. As the brain sample contained large amounts of 5hmC, the neural tissues of KOS14 patients are promising candidates for analysis in elucidating the role of 5hmC in the neurodevelopmental context. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13148-015-0124-y) contains supplementary material, which is available to authorized users.